Xiaomi in the internationalization process: failures and lessons - Wang, Kai (2021)
Along with the trend of globalization, the rise of the Chinese economy, and the encouraging policies published by the government, more and more Chinese companies started to walk across the border. However, there are always threats behind the opportunities. Xiaomi Technology Co. Ltd, which is conceived as one of the leading innovative tech companies, has achieved outstanding success in the domestic market of the mainland China, occupying the biggest Market share after establishing for 4 years, and obtaining profound influences for the whole telefone industry. Xiaomi started its internationalization process in 2013 and decided to be na international company. In this thesis, an introduction about industry background would be delivered, including how foreign multinationals like Samsung and Apple are influencing Chinese market, and how Chinese telephone companies like TCL, One plus is deciding to explore the oversea market in this situation. Moreover, the international practices of Xiaomi were described, ranging from the trial sales in Hong Kong and Taiwan to the complete launch to Southeast Asia and the Other markets. More importantly, three main problems Xiaomi has been exposed during its internationalization process were studied – The patent crisis, and the unsuccessful sales performance aboard. Xiaomi’s international expansion experiences in India and Brazil has been taken as an example to discuss and analyze, though secondary data, the selection of foreign market, the entry mode, the problems and solution of the dilemma that Chinese enterprises faced, aiming at offering a valuable lesson of experience to the other companies which may have the plan to start its internationalization process.